Type II insulin-like growth factor receptor is present in rat serum. - Kiess, W (1987)
We previously identified in fetal rat serum a component capable of specifically binding radiolabeled insulin-like growth factor type II (IGF-II) that is considerably larger than both the fetal (40 kDa) and the adult (150 kDa) carrier proteins. We now present immunologic and affinity crosslinking data to show that this binding species is the type II IGF receptor. Rat serum was gel-filtered on a Sephadex G-200 column (0.05 M NH4HCO3, pH 8), and 125I-labeled IGF-II (125I-IGF-II) binding was measured in individual column fractions. 125I-IGF-II binding activity was found in the void volume of the column in addition to the carrier protein regions. Competitive binding studies using 125I-IGF-II and binding activity from the Sephadex G-200 void volume showed the characteristics of the type II receptor: IGF-II was more potent than IGF-I, and insulin did not compete. Moreover, a specific anti-type II IGF receptor antibody (no. 3637) completely blocked 125I-IGF-II binding. 125I-IGF-I did not bind to the void volume pool, demonstrating the absence of the type I IGF receptor in rat serum. Affinity crosslinking of 125I-IGF-II to the Sephadex G-200 void volume material demonstrated a specific band at 210 kDa without reduction and at 240 kDa after reduction of disulfide bonds. The serum type II IGF receptor size was confirmed by immunoblotting the void volume material with antiserum 3637, which revealed a band slightly smaller (approximately 10 kDa) than the type II IGF receptor from rat placental membranes. Immunoquantitation by immunoblotting using pure type II IGF receptor from rat placental membranes as standard showed a developmental pattern. In fetal rat serum (19-days gestation) and in sera from 3-, 10-, and 20-day-old rats, the concentrations of receptor protein were similar (1-5 micrograms/ml). The level of the type II IGF receptor in serum declined dramatically between age 20 and 40 days, but the receptor was still measurable at age 12 mo. We conclude that the type II IGF receptor is present in rat serum and is developmentally regulated.